PENERAPAN MODEL PEMBELAJARAN READ-ANSWER-DISCUSS-EXPLAIN-CREATE (RADEC) PADA MATERI LARUTAN PENYANGGA DI SMAS INSHAFUDDIN BANDA ACEH - Hanum, Latifah; Zulfadli, Zulfadli; Nisa, Chairun (Lantanida Journal, 2023)
This study titled "Application of Read-Answer-Discuss-Explain-Create (RADEC) Model on Buffer Solution Material at SMAS Inshafuddin Banda Aceh " aims to explain activities, analyze learning results, and describe student responses. This qualitative descriptive study was carried out at SMAS Inshafuddin, with 20 participants chosen through purposive sampling from class XI IPA 1. Observing activities, learning outcome exams, and student response questionnaires on the RADEC learning model were used to collect data. The data analysis technique for student activities was collected by giving observers observation sheets, learning outcomes were obtained by giving them multiple-choice questions, and student responses were obtained by giving them a questionnaire. Data analysis revealed that student actions in the first meeting were 78.8% in the good category, 85.98% in the good category in the second meeting, and 92.86% in the very good category in the third meeting. In the good group, the completeness of student learning outcomes was 77.8%. The very good category received 92.25% of the student responses. Based on the study's findings, it is possible to infer that student activities have improved, student learning outcomes have been completed, and students have responded well to the introduction of the RADEC learning model.